PERAN GANDA ISTRI PETANI (Studi Kasus di Desa Perangian Kecamatan Baraka Kabupaten Enrekang) - Suparman Suparman (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The type of this research is a study case with qualitative desrictive aproach. the informant is chosen by purposive sampling technique, who as mother and farm worker. The data is obtained by employing Observation, Interview, and Documentation. The datais analysed by using descriptive qualitative analysis technigue. The results of the research reveal that factors causingthe farmer’s wife to do multiple roles arethe internal and external factors. The internal factors are the husband’s income connot fulfill the daily needs, not to mention the number of famillymembers. The external factors are the invorenment conditions of farming fields which need lots of workers, low education and lack of adequate skills causing no chance for others jobs. The forms of multiple roles as a mother are nurturing the children and husband, and as a wife educating the children and helping family’s economic matter. The impacts of multiple roles are difficulty in conducting her domestic jobs, less time to distribute equal time with multiple roles carried out, tiridness to conduct the job professionally, and complains to husband when she is tired due to multiple roles Keyword : farmer’s wife, multiple roles